Association of serum Klotho with tinnitus prevalence, duration and severity: A cross-sectional study in middle-aged and older adults. - Ke-Jiang Du; Bin-Yu Mo; Tao Hou; Long Chen; Deng-Rong Su; Shi-Hua Yin (PLoS ONE)
Background As an anti-aging protein, although studies increasingly suggest that the Klotho plays a role in the auditory system, the link between serum Klotho levels and tinnitus remains poorly characterized. The aim of this study was to investigate the associations between serum Klotho levels and tinnitus focusing on prevalence, duration and severity in middle-aged and older adults. Methods We performed a population-based cross-sectional study of individuals in the National Health and Nutrition Examination Survey (NHANES) 2009-2012 and 2015-2016. Univariable and multivariable logistic regression was used to evaluate the relationship between serum Klotho levels and tinnitus, with adjustment for potential confounders and further age-stratified analyses. Restricted cubic splines were applied to assess potential non-linearity in the dose-response relationship. Furthermore, Subgroup and interaction analyses were conducted to assess the consistency of this association. Results In this research of 3280 individuals aged 40-79 years with a median age of 55 (IQR: 48, 62) and 48% male participants, the median serum Klotho level was 779.80pg/mL. Multivariable logistic regression uncovered consistent inverse associations between serum Klotho levels and tinnitus incidence across progressively adjusted models (ORs: 0.68-0.70, p = 0.009-0.01). Age-based stratified analyses suggested the strongest effect was observed in individuals aged 50-59 years (full model ORs: 0.55, p = 0.046). A marginally significant protective effect was observed in the 60-69 age group (unadjusted OR=0.62, 95% CI: 0.39-1.00, p = 0.050). Serum Klotho levels showed no significant correlation with tinnitus severity, while a potential association with the duration of tinnitus was observed (p = 0.058). Additionally, restricted cubic spline analysis revealed a linear inverse association between Klotho and tinnitus risk stratified by age (all p for nonlinear >0.15). Finally, subgroup and interaction analyses revealed no significant effect modification (all p-interaction >0.1). Conclusion Serum Klotho concentrations showed a consistent inverse association with tinnitus prevalence in US adults, with the strongest effect observed in individuals aged 50-69 years.